Determinants and implications of crop production loss: An empirical exploration using ordered probit analysis. (September 2017) - Islam, Zeenatul; Alauddin, Mohammad; Sarker, Md. Abdur Rashid
Highlights: Explores farmers' perception of climate-induced crop loss. Identifies factors underlying farmers' perception of severity of crop loss. Finds severity of production losses to vary across three rice crops. Geophysical factors, institutional support, adaptation strategy drive loss severity. Strong support systems and scientific breakthroughs constitute key policy areas. Abstract: This study investigates farmers' perception about the severity of loss for three rice crops, identifies their determinants and explores policy implications based on findings. This research employs an ordered probit model to data collected from 1800 farm households from drought-prone and groundwater depleted areas of Bangladesh. This is the first study of its kind. Severity of rice production loss, while differing across all three rice crops, was higher for rain-fed crops. This was broadly consistent with available independent evidence. Geophysical factors, household characteristics, institutional and market accessibility, and household adaptation strategy were key determinants of crop loss. The impact of these factors was specific to the crop and severity of loss. This study has several policy implications involving market, R & D and institutional support based options. Strengthening support systems for institutional and market accessibility, and science driven climate change adaptation strategy including generation and wider dissemination of drought tolerant rice varieties, and enhancing farmers' capacity to change rice varieties on a regular basis, constitute key areas for policy intervention.